Transposable element exonization generates a reservoir of evolving and functional protein isoforms - Arribas, Yago A.; Baudon, Blandine; Rotival, Maxime; Suárez, Guadalupe; Bonté, Pierre-Emmanuel; Casas, Vanessa; Roubert, Apollinaire; Klein, Paul; Bonnin, Elisa; Mchich, Basma; Legoix, Patricia; Baulande, Sylvain; et al. (Cell, 2024)
Alternative splicing enhances protein diversity in different ways, including through exonization of transposable elements (TEs). Recent transcriptomic analyses identified thousands of unannotated spliced transcripts with exonizing TEs, but their contribution to the proteome and biological relevance remains unclear. Here, we use transcriptome assembly, ribosome profiling, and proteomics to describe a population of 1,227 unannotated TE exonizing isoforms generated by mRNA splicing and recurrent in human populations. Despite being shorter and lowly expressed, these isoforms are shared between individuals and efficiently translated. Functional analyses show stable expression, specific cellular localization, and, in some cases, modified functions. Exonized TEs are rich in ancient genes, whereas the involved splice sites are recent and can be evolutionarily conserved. In addition, exonized TEs contribute to the secondary structure of the emerging isoforms, supporting their functional relevance. We conclude that TE-spliced isoforms represent a diversity reservoir of functional proteins on which natural selection can act. [Display omitted] •Transposable element (TE) exonization expands the diversity of the human proteome•TE-spliced isoforms can have distinct functions compared with canonical isoforms•Exonized TEs can be evolutionarily conserved and add young sequences to ancient genes•Exonized TEs contribute to the overall secondary structure of proteins Transposable element exonization by unannotated splicing events produces stable protein isoforms with acquired functions that are subject to evolutionary selection.